2022
DOI: 10.1007/s11069-022-05307-w
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a pre-trained sentiment analysis (SA) classification model on tweets related to emergency response and early recovery assessment: the case of 2019 Albanian earthquake

Abstract: Traditionally, earthquake impact assessments have been made via fieldwork by non-governmental organisations (NGO's) sponsored data collection; however, this approach is time-consuming, expensive and often limited. Recently, social media (SM) has become a valuable tool for quickly collecting large amounts of first-hand data after a disaster and shows great potential for decision-making. Nevertheless, extracting meaningful information from SM is an ongoing area of research. This paper tests the accuracy of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Another study using the data from women living in Kocaeli (Turkey), investigated women's earthquake risk perception and factors helping to predict it by employing ordinary least square methods and revealed that the items that measure fear and financial perception have the highest mean among women's affective and cognitive risk perception factors [25]. The article [26] tested the accuracy of the pre-trained sentiment analysis (SA) model developed by the no-code machine learning platform MonkeyLearn through a confusion matrix where an overall accuracy (ACC) rate and a misclassification rate were 63% and 37% respectively using the text data of the three major earthquakes of Albania in 26th November 2019. Sentiment analysis has also gained attention during the analysis of the Covid-19 pandemic situation.…”
Section: Related Studymentioning
confidence: 99%
“…Another study using the data from women living in Kocaeli (Turkey), investigated women's earthquake risk perception and factors helping to predict it by employing ordinary least square methods and revealed that the items that measure fear and financial perception have the highest mean among women's affective and cognitive risk perception factors [25]. The article [26] tested the accuracy of the pre-trained sentiment analysis (SA) model developed by the no-code machine learning platform MonkeyLearn through a confusion matrix where an overall accuracy (ACC) rate and a misclassification rate were 63% and 37% respectively using the text data of the three major earthquakes of Albania in 26th November 2019. Sentiment analysis has also gained attention during the analysis of the Covid-19 pandemic situation.…”
Section: Related Studymentioning
confidence: 99%